PROGNOSTIC VALUE OF DYNAMIC THIOL-DISULFIDE HOMEOSTASIS IN PREDICTING HOSPITAL MORTALITY IN HYPOXEMIC RESPIRATORY FAILURE - Bilal İlanbey; Duygu Zorlu; Hacı Mehmet Çalışkan; Zamir Kemal Ertürk; Burak Çelik; Süleyman Ersoy; Kenan Güçlü (Rojan GÜMÜŞ, 2022)
Hypoxemic respiratory failure (HRF) has a PaO2 < 60 mmHg with normal or subnormal PaCO2. The gas exchange is impaired at the level of the alveolo-capillary membrane. HRF is associated with high mortality in hospital, and there is no diagnostic laboratory test to predict this mortality. This study evaluates the possibility of predicting mortality in HRF patients with dynamic thiol-disulfide homeostasis parameters, which are indicators of oxidation state. Sixty-two patients with HRF and 40 healthy controls were included in the study. Dynamic thiol-disulfide parameters were studied from the serum of all participants. Total and native thiol levels were significantly lower in the patients than in the controls (p < 0.05). Disulfide levels were higher in patients who died than survivors (p